PENINGKATAN PERAN AUDITOR DALAM PENCEGAHAN DAN PENDETEKSIAN FRAUD - Mimin Nur Aisyah (Jurnal Pendidikan Akuntansi Indonesia, 2006)
PENINGKATAN PERAN AUDITOR DALAM PENCEGAHAN DAN PENDETEKSIAN FRAUDSince the bankrupty cases of several big companies that involve their auditors in the accounting scandal, the auditor profession get strong pressure to improve their performance. Sarbanes Oxley Act of 2002 contains a comprehensive rule about corporate governance. It will increase the number of charges to white collar criminals. Fraud in the company is management’s responsibility, but auditors also have the responsibility to find and disclose it by make a plan and audit work to get a reasonable assurance whether financial statements were free from material misstatement, neither caused by error nor by irregularities. The evaluation of organizational condition, company structure and choices made is expected to help disclosing the motivation, opportunity and rationalization beyond the fraud of financial statements. To avoid the occurrence of fraud arises from motivation and opportunities, management should create a condusive environment in the company. On the other hand, auditors should also improve their competence, especially in fraud detection, by a strategic reasoning in audit risk valuation, audit planning and audit working. Strategic reasoning will be more challenging by the existence of strategic dependence in which the level of auditor’s expectation on manager’s action is affecting manager’s action.   Kata kunci : Fraud, auditor, strategic reasoning